Percepção de estigma e qualidade de vida em crianças com neoplasia - Araújo, Priscilla Cristhina Bezerra de (2012)
The increase in survival time and cure requires more extensive care about the quality of life of cancer patients, which begins soon after diagnosis. Thus, it seems reasonable to the emphasis on development of studies covering the psychosocial variables, such as stigma, treatment of childhood cancer aiming thereby to the attention of the overall needs of the child. Thus, this research aims to investigate the perception of stigma and quality of life in children with cancer. This is a cross-sectional research and understanding of the descriptive type, the type specimen being adopted for convenience. This consisted of thirty children with cancer and thirty children without chronic disease. The instruments used were the Quality of Life Questionnaire, the Perceived Stigma Scale and Technical Drawing Story with a Theme. The results indicate that the chronic condition, no interfered significantly in satisfaction with the quality of life in children with cancer and identified that the quality of life is not related to the stigma. Comparison with children with no chronic disease with infants with cancer, no significant differences were observed. However, the group mean contrast was lower, suggesting a greater impairment in quality of life of children with cancer compared to those without chronic disease. It is worth noting that the psychosocial effects and the limitations imposed by disease and treatment are presented as important factors in the design mode of subjective manifestations of children with cancer. Therefore, it is expected that knowledge elucidated by this study will assist, greatly to the promotion of improved emotional, biological and social development itself and the involvement of children with cancer treatment